2016
DOI: 10.1098/rsif.2015.1027
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale signatures of unconsciousness are consistent with a departure from critical dynamics

Abstract: Loss of cortical integration and changes in the dynamics of electrophysiological brain signals characterize the transition from wakefulness towards unconsciousness. In this study, we arrive at a basic model explaining these observations based on the theory of phase transitions in complex systems. We studied the link between spatial and temporal correlations of large-scale brain activity recorded with functional magnetic resonance imaging during wakefulness, propofol-induced sedation and loss of consciousness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
193
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 63 publications
23
193
0
2
Order By: Relevance
“…molecular motors acting within a cellular membrane). Considering the wide range of systems that can be tuned near criticality, we can exploit any other order parameter tuned near criticality in a given system, such as pH-value and particle concentration [29]. Since phase separations have been already widely found inside the human body [16,17] and some of them are known to be sources of diseases such as protein condensations [18], new biocompatible engines can be designed based on our critical engine that could be able to perform medical surgeries non-invasively such as the treatment of arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…molecular motors acting within a cellular membrane). Considering the wide range of systems that can be tuned near criticality, we can exploit any other order parameter tuned near criticality in a given system, such as pH-value and particle concentration [29]. Since phase separations have been already widely found inside the human body [16,17] and some of them are known to be sources of diseases such as protein condensations [18], new biocompatible engines can be designed based on our critical engine that could be able to perform medical surgeries non-invasively such as the treatment of arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the brain dynamics there is wide consensus on the connection between consciousness and criticality. See, for instance, [9,[16][17][18] and the recent review paper [19]. The electroencephalogram (EEG) signals are characterized by abrupt changes, called rapid transition processes (RTP), which are proved [20,21] to be renewal non-Poisson events, with ≈ 2.…”
Section: Complexitymentioning
confidence: 99%
“…The value of adjusts according to (11) from small values around 0.2 to a maximal value of 1.8, which is known to correspond to a supercritical condition in the case of the conventional DMM. When using the fine tuning control parameter approach we set = 1.8; the social system is far from the intelligence condition that according to a widely accepted opinion [9,[16][17][18][19]] requires criticality. (11) for the same regular two-dimensional network of Figure 1; red line: the time evolution of ( ) of the self-organized system described by the black under the influence of the weak noisy perturbation described in Section 4.…”
Section: Top-down Approach To Self-organized Temporal Criticalitymentioning
confidence: 99%
“…The terms local and global, when applied to neurocognitive architectures, generally refer to the spatial extent of information processing. A number of empirical studies have suggested that information processing during conscious mental activities is widely distributed ("global") across cerebral cortex regions and also associated with increased inter-regional communication [42][43][44]. Inspired by this, a number of neural network models have been studied in which conscious/effortful information processing is associated with computational processes involving the recruitment of hidden layers and hence widespread network activation of a "global workspace" [45,46].…”
Section: Past Suggestions For Computational Correlates Of Consciousnessmentioning
confidence: 99%